(untitled) (Nordic Journal of African Studies, 2011)
Scanning through the literature on diasporas one finds two opposing views. On the one hand diasporas are promoted as having the necessary education, experience and knowledge to contribute towards peace, stability and development, while on the other hand they are concurrently seen as fueling conflicts in their countries of origin. In the literature there seems to be a gap in explaining perceptions of local communities from the country of origin of the diaspora’s contributions. This article aims to analyze the interactions between the diaspora and the locals in the case of Somalia. It will be claimed that depending on the position and interests of the locals and the diaspora members, the diaspora’s activities can be either recognized or rejected. The perceptions are examined both from the diaspora’s and the local communities’ points of view and conditions under which the diaspora and the locals achieve mutual recognition are analyzed. This article is based on extensive empirical data which were collected through 144 interviews, 7 group discussions and participant observation in different parts of Somalia, the UK and Finland.